(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study delved into how both intrinsic and extrinsic factors can predict lecturers' anxiety and their willingness to use instructional technologies in teaching electrical courses at polytechnics in North-Central Nigeria. With the increasing push for digital integration in higher education, it’s crucial to understand the psychological and systemic elements that affect educators' adoption of technology in technical fields. The primary goal of this study is to explore how both intrinsic and extrinsic factors influence lecturers' anxiety and their willingness to use instructional technologies while teaching electrical courses in polytechnics located in North-Central Nigeria. This study adopted population size of 250 lecturers. A mixed-methods approach was utilized, blending quantitative surveys with qualitative interviews, targeting lecturers from selected public and private polytechnics in the region. This study employed multiple linear regression analysis. The results show that motivational elements, intrinsic motivation, level of anxiety, and suggestion all significantly increase lecturers’ anxiety. This indicates that certain motivational pressures such as personal drive, expectations, or performance-related suggestions can unintentionally heighten anxiety levels. While institutional support had a positive but insignificant effect, it shows that existing support structures are not strong enough to reduce anxiety. Extrinsic motivation had a negative but insignificant effect, suggesting that external rewards alone do not meaningfully reduce anxiety. Overall, the findings highlight the need for stronger institutional interventions and healthier motivational environments to reduce lecturers’ anxiety. Establish counseling and wellness units dedicated to managing academic stress and mental health. Encourage self-paced professional development rather than excessive self-imposed pressure. Avoid using high-pressure performance metrics without providing adequate support. Train administrators and supervisors to give encouraging, clear, and supportive suggestions. Provide meaningful rewards such as promotion opportunities, research grants, or reduced administrative workload. Introduce mindfulness, relaxation, and mental health awareness programs within the institution.